Upregulation of extrinsic and intrinsic apoptosis pathways in head and neck squamous cells by promotion of caspase activation by P13K inhibitor HCD – A systematic review. - Shunmugavelu, Dr. Karthik; Nallaiyan (M.D.S), Dr. Parthiban; S, Uma Bharathi (Student's Journal of Health Research Africa, 2026)
Background Constitutive activation of the phosphoinositide-3-kinase/protein kinase B (PI3K/Akt) pathway promotes tumor cell survival and resistance to apoptosis in head and neck squamous cell carcinoma (HNSCC). 16-Hydroxycleroda-3,13-dien-15,16-olide (HCD), a clerodane diterpene isolated from Polyalthia longifolia, has demonstrated pro-apoptotic activity through inhibition of PI3K signaling. This systematic review evaluated whether HCD activates intrinsic and extrinsic apoptotic pathways through caspase signaling in HNSCC models. Methods A systematic review was conducted according to PRISMA 2020 guidelines. PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar were searched using predefined Boolean combinations related to HCD, PI3K inhibition, and apoptosis. Two reviewers independently screened studies and extracted data. Eligible studies were original experimental investigations evaluating apoptosis-related endpoints, including caspase activation, Bax/Bcl-2 modulation, cytochrome-c release, PARP cleavage, reactive oxygen species generation, and PI3K/Akt signaling alterations. Due to heterogeneity in experimental models and outcome reporting, findings were synthesized using structured qualitative narrative analysis. Results Five in vitro studies met the inclusion criteria. HCD consistently reduced PI3K/Akt phosphorylation, increased oxidative stress, altered Bax/Bcl-2 balance, induced mitochondrial membrane depolarization, and activated caspase-9 and caspase-3. In oral squamous cell carcinoma models, activation of caspase-8 and upregulation of death receptor signaling indicated concurrent engagement of extrinsic apoptosis. Conclusion Available preclinical evidence indicates that HCD induces caspase-dependent apoptosis through suppression of PI3K/Akt signaling and activation of both mitochondrial and death receptor pathways. Future research Further experimental and translational studies, including in vivo investigations and clinical validation, are required to determine the therapeutic potential of HCD in head and neck squamous cell carcinoma.